Demographic characteristics, game playing time and factors affecting the achievements of e-sport players - Mustafaoğlu, Rüstem; Zirek, Emrah; Yasacı, Zeynal (Journal of Dependence, 2018)
Objective: The aim of this study was to investigate the e-sports players demographic characteristics, the reasons that directs them to the e-sports, playing time and personal and other factors affecting their achievements.Methods: The structured questionnaire was published on 42 game/forum sites where e-Sport athletes played/met, and those who volunteered to participate in the study were filled questionnaire.Results: A total 367 e-Sports players participated in the study. 96.5% of the participants were male and 77.1% were students. Among the reasons for dealing with e-sports, the passion for playing games in the first place (58.3%). The participants were interested in e-Sports for 4.5 years, and the weekly average duration of offline and online game playing time was 17.1 hours and 25.1 hours, respectively. Among the personal factors affecting achievement were team game (78.8%) and internet speed (91%) among equipment factors.Conclusion: In Turkey, e-Sports was found to be prevalent among young people aged 18 and under, males and students. The first personal factor that influenced the achievements of e-Sport players the team game and among equipment factors the speed of internet.
Keywords: e-Sports; video games; achievement; age